Enfermedad Cardiovascular y Perfil Lipídico en ancianos con factores de riesgo clásicos: Cardiovascular disease and lipid profile in elderly persons with classical risk factors (La U Investiga, 2018)
To establish the association between the occurrence of coronary event and the lipid profile in elderly patients (over 70 years old) with typical risk factors. A comparative study was carried out, where 40 patients were assigned to the case group with coronary disease (AMI-Angina) and 80 patients to the control group without coronary disease, both groups without statistically significant differences with respect to different variables (age, gender, comorbidities). or smoking), attended at the Endocrinology Service of the Specialties Hospital of the Armed Forces Nº1 Quito-Ecuador. The association between coronary event and high values of low density lipoproteins was statistically significant (OR: 4, CI: 1.31-12.74, p
Keywords: LDL cholesterol; cardiovascular risk; coronary syndrome